Faktor-Faktor yang Memengaruhi Terjadinya Stunting - Febriana Sari; Maria Magdalena Sinaga; Kismiasih Adethia; Inryani M.E Marpaung (Politeknik Baubau, 2022)
The incidence of short toddlers or commonly referred to as stunting is one of the nutritional problems experienced by toddlers in the world today. The percentage of stunting under five in North Sumatra Province is 7.4%, this is a challenge in carrying out activities that contribute to the achievement of stunting prevention targets, including the pandemic situation causing disruption of nutritional services, especially in health service facilities and posyandu due to restrictions on community mobility to prevent the spread of the Covid-19 virus. The purpose of this study was to determine the factors that influence the occurrence of stunting. Design This research was conducted using a cross sectional design. The sampling technique with a total sampling of 42 people. Bivariate analysis using chi square test. The results showed that there was a relationship between birth weight variables p=0.006, birth length p=0.002, exclusive breastfeeding p=0.025, economic status p=0.008 and stunting. For families who have children with LBW, short birth length can anticipate and provide good care for their growth and development. toddlers through communication, information and education, health promotion or counseling, workshops and others.